Seri Paduka Baginda Yang Dipertuan Agong Tuanku Syed Sirajuddin Putra Jamalullail : the installation of his Majestry and Malaysia Explained - 264775 Tan, Joo Lan; Khoo, Kay Kim, Profesor Emeritus Tan Sri Dato' Dr., 1937-2019, 456852; Tan, Teong Jin 297867 (Kuala Lumpur : Usahasama Seri Cemerlang, 2007)
Unknown;